RAD sequencing reveals genomewide divergence between independent invasions of the European green crab (Carcinus maenas) in the Northwest Atlantic. Issue 8 (14th March 2017) - Jeffery, Nicholas W.; DiBacco, Claudio; Van Wyngaarden, Mallory; Hamilton, Lorraine C.; Stanley, Ryan R. E.; Bernier, Renée; FitzGerald, Jennifer; Matheson, K.; McKenzie, C. H.; Nadukkalam Ravindran, Praveen; Beiko, Robert; Bradbury, Ian R.
Abstract: Genomic studies of invasive species can reveal both invasive pathways and functional differences underpinning patterns of colonization success. The European green crab ( Carcinus maenas ) was initially introduced to eastern North America nearly 200 years ago where it expanded northwards to eastern Nova Scotia. A subsequent invasion to Nova Scotia from a northern European source allowed further range expansion, providing a unique opportunity to study the invasion genomics of a species with multiple invasions. Here, we use restriction‐site‐associated DNA sequencing‐derived SNPs to explore fine‐scale genomewide differentiation between these two invasions. We identified 9137 loci from green crab sampled from 11 locations along eastern North America and compared spatial variation to mitochondrial COI sequence variation used previously to characterize these invasions. Overall spatial divergence among invasions was high (pairwise F ST ~0.001 to 0.15) and spread across many loci, with a mean F ST ~0.052 and 52% of loci examined characterized by F ST values >0.05. The majority of the most divergent loci (i.e., outliers, ~1.2%) displayed latitudinal clines in allele frequency highlighting extensive genomic divergence among the invasions. Discriminant analysis of principal components (both neutral and outlier loci) clearly resolved the two invasions spatially and was highly correlated with mitochondrial divergence. Our results reveal extensive cryptic intraspecific genomic diversity associated with differing patterns of colonization success and demonstrates clear utility for genomic approaches to delineating the distribution and colonization success of aquatic invasive species. Abstract : Here, we use RAD sequencing to, for the first time, quantify the genomic divergence between two independent invasions of European green crab to eastern North America, and discuss the implications of this research with respect to management of this invasive species.